Default Mode Network (DMN) for Human Five Senses and Sensory Environments - Hiroshi Bando; Akiyo Yoshioka; Yu Nishikiori; Masahiro Bando (Asploro Journal of Biomedical and Clinical Case Reports, 2026)
The default mode network (DMN) plays a crucial role in sensory perception. The primary roles of the DMN include preparing for crises, predicting future events, and organizing information and memories. It comprises brain regions such as the medial prefrontal cortex, posterior cingulate cortex, precuneus, and inferior parietal lobule. For the five senses, including visual, auditory, olfactory, gustatory, and tactile senses, the activation of a combined multisensory network is important. Such integration may foster a more natural and stable psychological state. From a psychosomatic health point of view, prescribing, adopting, and designing sensory environments may contribute substantially to supporting our daily wellness and happiness in the future.